Data security and security data : 27th British National Conference on Databases, BNCOD 27, Dundee, UK, June 29 - July 1, 2010. Revised Selected Papers - MacKinnon, Lachlan M. (Lecture notes in computer science, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 27th British National Conference on Databases, BNCOD 27, held in Dundee, UK, in June 2010. The 10 revised full papers and 6 short papers, presented together with 3 invited papers, 1 best paper of the associated event on Teaching, Learning and Assessment of Databases (TLAD), and 2 PhD forum best papers were carefully reviewed and selected from 42 submissions. Special focus of the conference has been "Data Security and Security Data" and so the papers cover a wide range of topics such as data security, privacy and trust, security data, data integration and interoperability, data management for ubiquitous and mobile computing, data mining and information extraction, data modelling and architectures, data provenance, dataspaces, data streaming, databases and the grid, distributed information systems, electronic commerce, enterprise systems, heterogeneous databases, industrial applications, infrastructures and systems, intermittently connected data, file access methods and index structures, managing legacy data, new applications and processes, parallel and distributed databases, peer-to-peer data management, performance modelling of ubiquitous data use, personal data management, query and manipulation languages, query processing and optimisation, scientific applications, semantic Web and ontologies, semi-structured data, metadata and xml, user interfaces and data visualisation, Web data management and deep Web, Web services, and workflow support systems.